A Realidade Virtual como uma ferramenta para o ensino da Geometria Molecular - Moura, José Avelino dos Santos (2010)
Nowadays, even more, the access to the use of Informatics as a support to human actions and tasks is extremely spread in schools, homes, industry and several other applications. Specifically in Education, the use of Informatics as a supporting tool to the teacher and students has been the focus of many research undertaken in this area. Several technologies can be used in the educational process. In this dissertation special highlight is given to Virtual Reality, as a tool which is able to present to students new ways of exploring knowledge when compared to traditional approaches (black board, solid objects, chalk). This dissertation presents Virtual Reality techniques as additional tools to the teaching of General Chemistry, specifically, molecular geometry. In order to understand Organic Chemistry, a great level of abstraction is required by the students, since a large number of visualization alternatives is possible, when dealing with molecular geometry. These must be understood and visualized. Thus, this dissertation intends to contribute by presenting a Virtual Reality based environment, where Hydrocarbon molecules can be visualized and explored in three dimensions, providing a better way to help students to learn this specific subject.